Double‐Thinking and Contradictory Arrangements in Iranian Law and Society. (9th April 2018) - Banakar, Reza
Abstract: Although thinking double thoughts and living dual lives are not specifically Iranian traits, Iranians have, nevertheless, become more susceptible to them for historical reasons, which may be traced back to when Persians became Muslims. The gradual normalization of double‐thinking over the centuries has given rise to social and political patterns of behavior and institutional arrangements which oscillate between opposing regimes of truths and different sets of ethical concerns, often without merging them into a new process. Once double‐thinking is normalized at the level of society, it helps people to cope with the cognitive dissonance they experience in circumstances where it is difficult to change attitude and behavior. It also affects the organization of society by making contradictory arrangements appear normal. It promotes reflexive thinking and subversive action as much as it facilitates misrecognition of sociopolitical suppression and legitimization of symbolic violence. This state of affairs generates a form of modernity which appears, at least on the surface, to be comfortable with contradictory social arrangements, while deep down it remains ill at ease with its inner contradictions.